Role of interleukin-4, the chemokine CCL3 and its receptor CCR5 in neuropathic pain. (September 2016) - Sun, Shiyu; Chen, Dan; Lin, Fuqing; Chen, Minghui; Yu, Hongli; Hou, Lengchen; Li, Cheng
Highlights: Expression of both CCL3 and CCR5 was increased during CCI. Activation of microglia was observed after CCI. Injection of the anti-IL-4 or CCL3-neutralizing antibody could ease the CCI-induced inflammatory response. Knockout of CCR5 suppressed CCI-induced neuropathic pain. Abstract: Cytokines and chemokines are involved in chronic pain syndromes, and their expression is altered in injury-induced neuronal pain pathways. However, the exact cytokines/chemokines involved and their mechanism of action remain to be determined. In this study, we investigated the role of interleukin-4 and the chemokine/chemokine receptor pair CCL3/CCR5 in a mouse model of chronic constriction injury (CCI)-induced neuropathic pain. Neuropathic pain was induced by surgical ligation of the sciatic nerve and assessed by measuring thermal hyperalgesia and mechanical allodynia using a plantar test and a dynamic plantar esthesiometer. The underlying mechanisms were investigated by real-time quantitative reverse transcription polymerase chain reaction, western blotting, immunohistochemistry, ELISA, and histopathology. CCI-induced neuropathic pain was associated with CCL3 and CCR5 upregulation and microglial activation. Intrathecal injection of the anti-inflammatory cytokine interleukin-4 or CCL3-neutralizing antibody alleviated CCI-induced inflammation, suppressing the CCI-induced upregulation of tumor necrosis factor-α and interleukin-1β in the serum and spinal cord, restoring the CCI-induced upregulation of CCL3 and CCR5, and suppressing the CCI-induced activation of p38 mitogen-activated protein kinase. Knockout of CCR5 also suppressed CCI-induced neuropathic pain. Since the upregulation of chemokines and cytokines is directly or indirectly involved in chronic pain after nerve injury, these molecules are potential therapeutic targets in the treatment of neuropathic pain.